Theory-methodological bases of general secondary education development prognostication. - Onyshchuk Lyudmila (Borys Grinchenko Kyiv Metropolitan University, 2018)
In the article, based on the analysis of the system of means of scientific cognition and critical understanding of the features of pedagogical prognostication as a specific type of scientific research and form of concretization of scientific prognostication, the results of pedagogical knowledge systematization prognostication highlighted. In the research format the ideas, theories, positions, patterns and principles that reflect the features of the object and subject of research scientifically interpreted. It was clarified that the development of theoretical principles for forecasting the development of general secondary education is connected with solving problems of educational and pedagogical prognostication as a branch of pedagogical science and using an interdisciplinary approach to substantiating the strategy of its development; signs of the scientific process and the result of forecasting the development of general secondary education is the nature of purpose-setting, the distinction of a special object of forecasting, the use of his means of knowledge, the uniqueness of terms and concepts; for the construction of the conceptual image of a certain element of science (in the research format - the conceptual image of the institution of education), in addition to imperative arguments and emotional arguments, it is necessary to reveal and substantiate the main characteristics of pedagogical forecasting. The links between studied pedagogical phenomena and processes reflected in the points of the Prediction Concept of General Secondary Education Development, program of the cyclical seminar «Theoretical and methodological fundamentals of preparing subjects of educational activity for the development of forecasts». This will facilitate the formation in subjects of government core, system-making views on the prospects for the development of general secondary education